First record of notoedric mange in ocelot (Leopardus pardalis Linnaeus, 1758) in the amazon region, Brazil - Scofield,Alessandra (2011)
This paper describes a case of notoedric mange in an ocelot (Leopardus pardalis) in the Brazilian Amazon region. A young male of approximately four months of age that was illegally kept as a pet was apprehended in Altamira, State of Pará, northern Brazil. The animal was transported to the Mangal das Garças Park in the state's capital city of Belém. The ocelot had pruritus and lesions suggestive of scabies in the head. Skin scraping material was examined under optic microscopy. There was seen a large number of eggs, larvae, nymphs and adult mites. The mean female and male sizes were 230.2 × 200.4 µm and 137.6 × 104.9 µm. Based on the morphologic characteristics and morphometric analysis, this mite was classified as Notoedres cati. This is the first report of notoedric mange in L. pardalis from Brazilian Amazon.